Sleep and circadian disruption and the gut microbiome-possible links to dysregulated metabolism. (April 2021) - Withrow, Dana; Bowers, Samuel J.; Depner, Christopher M.; González, Antonio; Reynolds, Amy C.; Wright, Kenneth P.
Abstract: Insufficient sleep and circadian misalignment are associated with adverse metabolic health outcomes. Alterations in gut microbial diversity occur with insufficient sleep and circadian misalignment, which can lead to modifications in microbial structure and function. Changes in microbially produced and modified metabolites such as short chain fatty acids and secondary bile acids may contribute to chronic inflammation, positive energy balance and endocrine changes, and represent potential mechanisms linking insufficient sleep and circadian misalignment with metabolic dysregulation. Literature primarily from the last two years is reviewed here, examining the impact of sleep and circadian rhythms and their disruption on the gut microbiome in human and non-human models, with an emphasis on the hypothesis that the altered gut microbiome may be one pathway by which insufficient sleep and circadian misalignment dysregulate metabolism.